Cardio-facio-cutaneous Syndrome with Severe Inflammatory Cutaneous Lesions: Dramatic Effect of Dupilumab - Sara A. Altandi; Pol A. Apoil; Juliette Mazereeuw-Hautier; Maella Severino-Freire (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)